Time and event in Amerindian onirocritic: a bibliographic review - Shiratori, Karen (Revista de Antropologia, 2022)
This article consists of a bibliographical review of the ethnological literature on dreams dedicated to the indigenous peoples of the South American Lowlands. The main thread of the exposition is the analysis of the dream event, the result of the soul's wanderings, and its influence on waking life. I claim that, as real events - not restricted to individual psychology - the distinct relations that the soul establishes with its dream interlocutors directly influence the interpretation of dreams and the effects they have on waking life. By considering the inadequacy of a conceptual repertoire based on the psychoanalytic method and on the notions of omen, fate and fatality, I seek a conception of onirocritic that includes the idea of an open and reversible time. The reflection that I propose is organized in two moments: (I) the dream as a diagnosis of ongoing events and (II) the manipulation of the possibilities engendered as virtuality.